Change management 2020 - Hakanpää, Tommi (My University, 2020)
Change is inevitable in today’s business world. Organizations are developing and trying to cope with challenges which are brought up by globalization and digitalization. Change processes themselves are occur-ring more often and their tempo keeps accelerating. Current literature present models and frameworks which can be used, by organizations and management, to execute change processes. This thesis explores ways how change is managed in real-life situations and what are most important aspects of change management. To be able to answer these questions, this thesis will first analyse existing literature and present most well-known models of change management. Study focuses on interviewing four leaders that have been managing changes during their careers. The method used in this study is qualitative research method. Interviews were carried out with theme-based interviews. Data was collected from four different interviews that lasted around one hour each. Data was collected by recording interviews. Data was transcribed to paper after interviews, which then was analysed. Study found out that there are similarities with many theoretical change models and the findings of this research. A new change model was generated, and it is based on analysed data. As a theoretical contribution to the existing literature, this thesis provides a new model that can be used in change situations. Furthermore, study offers a cross-section on how changes are managed today. The managerial implications in this study, provide new practical framework which can be used as a part of change management work. This framework helps spread knowledge on the change management in action.
Keywords: change; leadership (activity); change management (leadership); organisational changes; fi=Johtaminen ja organisaatiot|en=Management and Organization|; Master’s Programme in Strategic Business Development